Queue backlog as a node metric for RPL protocol - Abdullah M. A, Awad; Hassan Abdalla Hashim, Aisha; Ab Rahim, Rosminazuin (International Conference on Computer & Communication Engineering, 2016)
The current de-facto routing protocol over WSN developed by IETF Working Group (6LOWPAN) named as Routing Protocol for Low Power and Lossy networks (RPL) [1], to enable IPv6 packets carrying over IEEE 802.4 and to empower the usage of IoT over WSN. Because of the potential large networks, number of nodes and the fact that multiple coexisting applications will be running in the same physical layer, RPL in the network layer faces throughput challenges. For the purpose of overcoming these problems many researchers focused on multipath solutions including a Back-Pressure routing protocol for data collection called BackIP [2], however it shows a superior throughput performance, BackIP have shortcomings of higher delay and limited applicability. In this paper, we introduce a node metric based on nodes Queue Backlogs for RPL protocol, which leads to better throughput performance while maintaining the delay and the ability to use with the different network applications. This metric depends on the Packet Queue length of the nodes with the consideration of other link and node metrics, like ETX or Energy usage, leading to better load balancing in the network. Moreover we discuss the needed design changes to enable our metric to perform in an efficient way. Keywords-IOT, RPL, WSN, Back Pressure, Queue Backlog, Objective Function